Impact of Influenced Online Reviews and User-Generated Content on Customer Satisfaction Perception in E-Commerce Consumers - P Sasikumar; T. M. Hemalatha (Balai Publikasi Indonesia, 2026)
In today’s digital marketplace, online reviews, and user-generated content have become powerful influences on consumer behaviour, particularly in the e-commerce sector. This study explores how online reviews, customer testimonials, product ratings, images, and videos shared by users affect customer satisfaction perception among e-commerce consumers. As consumers increasingly rely on the opinions and experiences of others before making a purchase, understanding the role of these digital inputs is critical for businesses aiming to improve customer satisfaction. The research is based on a Quantitative Methods to survey responses from 300 e-commerce users with insights through Google Forms. The results indicate that the clarity, authenticity, and helpfulness of online reviews significantly impact how consumers perceive the quality of products and services. Additionally, user-generated images and videos increase buyer confidence and satisfaction by offering real-world evidence of product performance. The study highlights the importance for e-commerce platforms to actively encourage and manage customer feedback and content sharing. Businesses that promote transparent and engaging user content can enhance consumer trust, improve satisfaction levels, and reduce purchase hesitation. These findings offer practical value to marketers and platform designers seeking to strengthen the online shopping experience.